Digital repository of associations between environmental variables: A new resource to facilitate knowledge synthesis. (June 2015) - Ziegler, C. Richard; Webb, J. Angus; Norton, Susan B.; Pullin, Andrew S.; Melcher, Andreas H.
Highlights: Environmental associations are commonly used in assessments and synthesis studies. Such associations often take the form of causal or stressor–response relationships. We are developing a digital repository of associations gathered from research studies. The repository will improve environmental management and metrics of research impact. Abstract: Responsible care and management of Earth's resources requires scientific support, but the pool of underused research is growing rapidly. Environmental science research studies describe associations between variables (e.g. statistical relationships between stressors and responses). We propose open-access and online sharing of such associations. This concept differs from various efforts around the world to promote sharing of primary research data, but holds similar goals of improved use of existing knowledge. The initiative is made possible by recent developments in information technology and evolving online culture (e.g. crowdsourcing and citizen science). We have begun to connect existing projects that catalog and store associations, thereby moving toward a single virtual repository. Researchers and decision makers may share and re-use associations for myriad purposes, including: increasing efficiency and timeliness of systematic reviews, environmental assessments and meta-analyses, identifying knowledge gaps and research opportunities, providing evolved metrics of research impact, and demonstrating connections between research and environmental improvement.